The Health Benefits of Sexual Expression. Issue 4 (2nd October 2021) - Gianotten, Woet L.; Alley, Jenna C.; Diamond, Lisa M.
Abstract: Objective: Sexual activity is a fundamental human function with short-term and long-term emotional, social, and physical benefits. Yet within healthcare, sexuality has been marginalized and many HCPs are unaware of its beneficial implications for immediate and long-term health. Methods: To challenge this assumption we combined the data that already had been collected by the authors with an extensive search of articles on the various health benefits of sexual activity. The results of this process are displayed according to short-term, intermediate-term, and long-term benefits with some explanation about potential causal relationships. Results: For the time being, it cannot yet be proved that "good sex promotes good health" since good health also favors good sex. Conclusions: Despite lacking such convincing evidence, the article concludes with recommendations for the relevant professions. The balance of research supports that sexuality anyhow deserves greater attention among HCPs and that sexuality research needs better integration within health research.